2019
DOI: 10.1016/j.diff.2019.03.002
|View full text |Cite
|
Sign up to set email alerts
|

A pivotal role of androgen signaling in Notch-responsive cells in prostate development, maturation, and regeneration

Abstract: Androgen signaling is essential for prostate development, morphogenesis, and regeneration. Emerging evidence also indicates a regulatory role of Notch signaling in prostate development, differentiation, and growth. However, the collaborative regulatory mechanisms of androgen and Notch signaling during prostate development, growth, and regeneration are largely unknown. Hairy and Enhancer of Split 1 (Hes1) is a transcriptional regulator of Notch signaling pathways, and its expression is responsive to Notch signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
5
1
Order By: Relevance
“…It has been recently identified that the NOTCH pathway is not a simple linear sequence of events, as it can have crosstalk with other pathways to construct an extremely complex network [32]. Though AR pathway was crucial for PCa progression and involved in NOTCH signaling activation in PCa cells [19], we did not observe alterations in AR-dependent transcriptional activity after direct coculture with TAMs. Interestingly, we did not observe alterations in NOTCH ligands and receptors after direct coculture.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…It has been recently identified that the NOTCH pathway is not a simple linear sequence of events, as it can have crosstalk with other pathways to construct an extremely complex network [32]. Though AR pathway was crucial for PCa progression and involved in NOTCH signaling activation in PCa cells [19], we did not observe alterations in AR-dependent transcriptional activity after direct coculture with TAMs. Interestingly, we did not observe alterations in NOTCH ligands and receptors after direct coculture.…”
Section: Discussioncontrasting
confidence: 60%
“…Although recent studies demonstrated that AR signaling was involved in NOTCH signaling activation [19], GSEA results did not indicate that PCa cell AR signaling was significantly changed in a direct contact manner (Figure S3A). In addition, AR and PSA protein expression was not altered after direct contact (Figure S3B).…”
Section: M2 Macrophages Direct Contact Activates the Pca Notch1 Pathw...mentioning
confidence: 71%
“…Long-term testosterone enanthate treatment increased the expression of activated Notch1 in muscle satellite cells of older men consistent with increased satellite cell replication [28]. The importance for androgen-Notch interaction for the course of prostate development and morphogenesis was also demonstrated [29,30]. DeFalco et al [31] found that in mice testosterone plays a role in maintaining the balance between progenitor cells and differentiated fetal Leydig cells, regulating levels of JAG1 and Notch2.…”
Section: Of 22mentioning
confidence: 90%
“…Slides were developed with fluorescent-conjugated secondary antibodies and then mounted with coverslips using Vectashield Mounting Medium with DAPI (H-1200, Vector Laboratories). The mTmG assay was performed as previously described [48]. Briefly, sections from OCT embedded tissues were washed with PBS, pH 7.3, and then developed with Vectashield Mounting Medium with DAPI (H-1200, Vector Laboratories).…”
Section: Methodsmentioning
confidence: 99%